Localized Delivery of Mechano-Growth Factor E-domain Peptide via Polymeric Microstructures Improves Cardiac Function following Myocardial Infarction - Peña, James R. (Biomaterials, 2015)
The Insulin like growth factor-I isoform mechano-growth factor (MGF), is expressed in the heart following myocardial infarction and encodes a unique E-domain region. To examine E-domain function, we delivered a synthetic peptide corresponding to the unique E-domain region of the human MGF (IGF-1Ec) via peptide eluting polymeric microstructures to the heart. The microstructures were made of poly (ethylene glycol) dimethacrylate hydrogel and bioengineered to be the same size as an adult cardiac myocyte (100×15×15 μm) and with a stiffness of 20 kPa. Peptide eluting microrods and empty microrods were delivered via intramuscular injection following coronary artery ligation in mice. To examine the physiologic consequences, we assessed the impact of peptide delivery on cardiac function and cardiovascular hemodynamics using pressure-volume loops and gene expression by quantitative RT-PCR. A significant decline in both systolic and diastolic function accompanied by pathologic hypertrophy occurred by 2 weeks which decompensated further by 10 weeks post-infarct in the untreated groups. Delivery of the E-domain peptide eluting microrods decreased mortality, ameliorated the decline in hemodynamics, and delayed decompensation. This was associated with the inhibition of pathologic hypertrophy despite increasing vascular impedance. Delivery of the empty microrods had limited effects on hemodynamics and while pathologic hypertrophy persisted there was a decrease in ventricular stiffness. Our data show that cardiac restricted administration of the MGF E-domain peptide using polymeric microstructures may be used to prevent adverse remodeling of the heart and improve function following myocardial infarction.